From Clean Water to Casinos: Why Sovereignty is Important to Native Americans - Neuman, Lisa (Maine Policy Review, 2004)
Lisa Neuman’s commentary provides a further perspective on Native American sovereignty, focusing especially on how the situation in Maine compares with that of tribes elsewhere in the United States.